PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN KERINCI: RIZA NOVERHADI PUTRA, SE - RIZA NOVERHADI (JURNAL ADMINISTRASI NUSANTARA, 2021)
This study aims to determine how much influence the compensation, work motivation work environment has on employee performance in the Kerinci district education office. The analytical method used is regression analysis and correlation analysis. The results of the analysis show that the compensation, work environment and work motivation variables have a significant positive effect on employee performance variables, together. The amount of Adjusted R Square is 0.682. This means that 68.2% of the variation in employee performance can be explained by the three independent variables of compensation, work environment and work motivation. While the remaining 31.8% is explained by other variables outside this study such as job satisfaction, work performance and others.